Inhibition of Indoxyl Sulfate-Induced Reactive Oxygen Species-Related Ferroptosis Alleviates Renal Cell Injury In Vitro and Chronic Kidney Disease Progression In Vivo - Li-Ting Tsai; Te-I Weng; Ting-Yu Chang; Kuo-Cheng Lan; Chih-Kang Chiang; Shing-Hwa Liu (MDPI AG, 2023)
The accumulation of the uremic toxin indoxyl sulfate (IS) is a key pathological feature of chronic kidney disease (CKD). The effect of IS on ferroptosis and the role of IS-related ferroptosis in CKD are not well understood. We used a renal tubular cell model and an adenine-induced CKD mouse model to explore whether IS induces ferroptosis and injury and affects iron metabolism in the renal cells and the kidneys. Our results showed that exposure to IS induced several characteristics for ferroptosis, including iron accumulation, an impaired antioxidant system, elevated reactive oxygen species (ROS) levels, and lipid peroxidation. Exposure to IS triggered intracellular iron accumulation by upregulating transferrin and transferrin receptors, which are involved in cellular iron uptake. We also observed increased levels of the iron storage protein ferritin. The effects of IS-induced ROS generation, lipid peroxidation, ferroptosis, senescence, ER stress, and injury/fibrosis were effectively alleviated by treatments with an iron chelator deferoxamine (DFO) in vitro and the adsorbent charcoal AST-120 (scavenging the IS precursor) in vivo. Our findings suggest that IS triggers intracellular iron accumulation and ROS generation, leading to the induction of ferroptosis, senescence, ER stress, and injury/fibrosis in CKD kidneys. AST-120 administration may serve as a potential therapeutic strategy.